Pengembangan Daya Tarik Wisata Kunjung Museum Melalui Wahana Edukasi Di Museum Pura Pakualaman Yogyakarta - R.Jati Nurcahyo; Yulianto (Journal of Tourism and Economic, 2019)
For recent years, museum has played a strategic role in developing the knowledge of general society. This is due to its functions as a place to preserve and communicate cultural sources as well as a facilitator of studies and researches aiming at education mission and attractive alternative of recreation objects for the society. If it is well managed, the Yogyakarta Puro Pakualaman Museum is a potential site for the Entrance Gate and Landmark for the city of Yogyakarta as a special region. This research used the analyses of descriptive qualitative and interpretative. The collected data were obtained through analysis of documents, observations, and interviews. The analysis technique is interpreting the data so the understanding of the data is in accordance with the general objective of the research. The result of the study shows that the development of the Yogyakarta Puro Pakualaman Museum as a part of tourism destination through its function as education media can increase the visit to the museum.